Factors Affecting Fishers’ Income In Sibolga City - Rinaldi, Muammar; Harahap, Anita; Nugrahadi, Eko Wahyu; Hutasuhut, Saidun (Advances in Social Sciences Research Journal, 2019)
This study aims to investigate: (1) the effect of asset ownership on the income of fishers in Sibolga City, (2) the effect of the level of education on the income of fishers in Sibolga City, (3) the effect of working hours on fishing income in Sibolga City, (4) the effect of work experience on the income of fishers in Sibolga City. The population in this study were outboard motor fishers <5GT with traditional fishing gear in the form of nets in Sibolga City. The sampling technique is purposive sampling with a sample size of 90 fishers. Data was collected through an open-ended questionnaire. The results of the study found that: 1) asset ownership partially had a significant effect on the income of fishers in Sibolga City. 2) the level of education partially has a significant effect on the income of fishers in Sibolga City. 3) Working hours partially have a significant effect on the income of fishers in Sibolga City. 4) Partial work experience has a significant effect on the income of fishers in Sibolga City. 5) asset ownership, education level, working hours at sea, and work experience simultaneously have a significant effect on the income of the fishers in Sibolga City.